Lokal Wisdom Sebagai Basis Pendidikan Bangsa - Ngimadudin Ngimadudin (Edification Journal : Pendidikan Agama Islam, 2021)
Caring for the nationality is managing the unitary State of the Republic of Indonesia into "gemah ripah loh jinawi toto tentrem kertoraharjo". In terms of Indonesianness, it is a sentence which is an expression to describe the state of the Indonesian Mother Earth. Gemah ripah loh jinawi means (abundant natural wealth) while toto tentrem karto raharjo (serene condition). Or in the Arabic sense it becomes baldattun toyyibatun wa robbun ghoffur. This expression does not necessarily happen when the management of the State deviates from the khittoh of the prosperity of the nation and the State. Local wisdom is the essence that must be able to be defended amidst the storms of global ideology that ignore human values. When the younger generation begins to forget the historical and cultural roots from which they came from, they will get increasingly lost in the search for their identity.